(untitled) (PAKISTAN JOURNAL OF LAW, ANALYSIS AND WISDOM, 2024)
Ship-source pollution is a maritime menace which continues to harm the marine environment and also cause damage to persons and property, in particular, in the happening of a serious oil spill. The international law governing such pollution is almost entirely contained in conventions addressing both the private and the public maritime law. The primary and the most important intend of this paper is to address the private law side of the ship-source pollution equation focusing on a comparative analysis of the legal regimes of Pakistan, a common law jurisdiction, and China which belongs to the civil law tradition. Incidentally, both states are parties to the Civil Liability Convention, 1992 (CLC) but whereas China is also a party to the Bunkers Convention, 2001, Pakistan is not. Neither of the two states is a party to the Fund Convention, 1992 but Pakistan is looking to enter that convention. China operates its own national fund to provide compensation to pollution victims who remain uncompensated under the CLC 1992 scheme. Also, neither state is a party to the HNS Convention of 1996 modified by its 2010 Protocol. This paper provides an overview of the liability and compensation regimes of both states pursuant to the CLC 1992 and examines the national legislation of both states in comparative perspective. In conclusion, lacunae in the law of both jurisdictions are pointed out and commensurate proposals for improvement and refinement of their legal regimes are made.